(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Radiology nursing occupies a pivotal role in modern healthcare, bridging the gap between technological advancements and patient-centered care. This article explores the ethical considerations inherent in radiology nursing practice, focusing on patient privacy, radiation safety, technological competence, and patient advocacy. Upholding strict standards of confidentiality and privacy, radiology nurses safeguard patient information while facilitating effective communication among healthcare providers. Advocating for dose optimization and adherence to safety protocols, radiology nurses prioritize patient safety in the face of ionizing radiation exposure. Technological competence and integrity are essential attributes, requiring continuous education and ethical reflection to navigate rapidly evolving technologies with professionalism. Patient advocacy lies at the heart of radiology nursing practice, promoting informed consent, comfort, safety, continuity of care, and patient empowerment throughout the imaging process. By embracing these ethical imperatives, radiology nurses uphold the highest standards of professionalism, integrity, and compassion in the delivery of patient care.